Comparative study on protein expression of chicken meat between Malaysian broilers and indigenous chicken - Abu Hassan, Muhamad Shafiq; Muhamad Bunnori, Noraslinda (2014)
High consumer demand towards poultry meat has increased the production of broilers chicken.Due to high feed conversion ratio in broilers and administration of antibiotics in their feeds, broilers undergoes rapid juvenile growth in short time. The rapid growth has brought many health issues including metabolic diseases and other defects that could alter the meat quality. Thus, proteomics approach will be done to compare the protein profile between broilers and indigenous chicken meat. Two types of meat sample from aforementioned chickens were homogenized with extraction buffer and quantified by using Bradford assay. Then, the protein samples were examined by using SDS-PAGE and further resolved by using 2D-PAGE. Highest protein expressed distributed between 40-50 kDa on SDS-PAGE and predicted to be actin and myosin. 2D-PAGE result showed that three protein spots were expressed higher in broilers compared to indigenous chicken. The candidates for this proteins are Serotransferrin (pI:6.7; mW:50-75 kDa), myosin binding protein (pI:5-6; mW: 50-75 kDa) and T-complex protein 1 subunit epsilon (pI:5-6; mW: 50-75 kDa). In conclusion, three proteins have been identified and it may contribute to the changes of meat quality in broilers.